2020
DOI: 10.4164/sptj.57.4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ionomer Adhesion Ratio of Catalyst Layer on Electrode Characteristics of Polymer Electrolyte Fuel Cell

Abstract: Optimization of the catalyst layer structure is necessary to realize high performance and low cost of a polymer electrolyte fuel cell (PEFC). The catalyst layer is normally composed of Pt/C powder and an ionomer. The adhesion state of ionomer to Pt/C powder not only changes the proton transport route but also influences the microstructure of the electrode, which is an important factor in controlling cell performance. In this study, in order to investigate the adhesion state of ionomer, we developed the new mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We have reported that a PBI layer coated on the carbon surface facilitated Nafion adsorption and enabled homogeneous ionomer distribution in the CL, 62 thus we consider that ionomer distribution in the MEAs is homogeneous throughout the CL. The ionomer content was evaluated using TGA according to a reported procedure, 55 in which the sheets were heated from 30 to 550 °C under a N 2 flow, followed by isothermal heating at 550 °C for 10 min to allow complete decomposition of the Nafion ionomer. Finally, the sample was heated from 200 to 900 °C under an air flow to decompose the CNTs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that a PBI layer coated on the carbon surface facilitated Nafion adsorption and enabled homogeneous ionomer distribution in the CL, 62 thus we consider that ionomer distribution in the MEAs is homogeneous throughout the CL. The ionomer content was evaluated using TGA according to a reported procedure, 55 in which the sheets were heated from 30 to 550 °C under a N 2 flow, followed by isothermal heating at 550 °C for 10 min to allow complete decomposition of the Nafion ionomer. Finally, the sample was heated from 200 to 900 °C under an air flow to decompose the CNTs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sample was then heated to 900 °C at an air flow rate of 300 mL min −1 and a heating rate of 10 °C min −1 . 55 Transmission electron microscopy (TEM) was performed using a JEM-2010 microscope (JEOL, Tokyo, Japan) operated at 120 kV. X-ray photoelectron spectroscopy (XPS) was performed using an AXIS-ULTRA DLD spectrometer (Shimadzu, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…for 24 h at 25 °C to incorporate ionomer into the sheets, ionomer content was evaluated using TGA according to the reported procedure 55 , in which the sample was heated from 30 °C to 550 °C under N2 flow, followed by isothermal heating at 550 °C for 10 minutes to allow complete decomposition of Nafion ionomer. Finally, the sample was heated from 200 °C to 900 °C under air flow to decompose the CNTs (Figure S5a).…”
Section: Fabrication Of Mea and Characterizationmentioning
confidence: 99%